KONSELING PASTORAL PENERIMAAN ANAK PADA KEHADIRAN ORANGTUA TIRI DI KELURAHAN BAHU KECAMATAN MALALAYANG SATU - Hesky C Opit; Ryanto Fadly Sumendap; Diana Sari Yosepin Lakumani (POIMEN Jurnal Pastoral Konseling, 2022)
At this time, we often encounter in family life various problems, such as divorce. Divorce affects not only the couple but also the children. After the divorce, the parents decided to marry again. When parents decide to remarry, not all children can accept it. There are children who cannot accept the existence of stepparents, but there are also those who can accept it. The purpose of writing this journal is to determine pastoral assistance to the acceptance of children who have stepparents. Researchers looked at how the response of children with stepparents, what is the reaction of children who have stepparents, especially a daughter on the shoulder of the District Malalayang one. Researchers use case study research methods, more precisely descriptive case studies. As for the data collection is done by interviewing the subject of research.